IMPLEMENTASI HADIS ZIARAH MAKAM SYUHADA TERHADAP TRADISI HAUL ABAH GURU SEKUMPUL DI MARTAPURA, KALIMANTAN SELATAN - Anwar, Muhammad Khoirul; Fitriyani, Nita; Hasan, Siti Jamilah (JIQTA: Jurnal Ilmu Al-Qur'an dan Tafsir, 2023)
This article aims to analyse the implementation of the Prophet Muhammad's hadith about the pilgrimage to the martyr's grave in the tradition of Haul Abah Guru Sekumpul in Martapura. The research involves literature data and interviews with tradition actors. Then the data was analysed using Max Weber's social action theory. The findings of this research are that the tradition of Haul Abah Guru Sekumpul in Martapura is a category of traditional community action that is claimed to have theological roots from the Prophet Muhammad's hadith when visiting the graves of the martyrs. On the other hand, the tradition is believed to have affective meaning, which for the community is considered as a means of providing blessings for those who attend, or those who participate in the implementation of the event. From the social meaning, the tradition of Haul Abah Guru Sekumpul also has elements of mutual cooperation, togetherness, mutual respect and emulating the struggle.